Activist hedge funds and firm disclosure1. Issue 1 (8th October 2015) - Chen, Jing; Jung, Michael J.
Abstract: This study examines whether firms' disclosure decisions are affected by the presence of activist hedge funds. Using a large sample of firms that experienced increases in ownership by activist hedge funds, we find that firms are more likely to cease providing financial guidance or reduce the information in the guidance in the quarter subsequent to new investment by activist hedge funds. These results hold even for firms that experienced good quarters and consistently provided guidance in previous quarters. Since guidance has been shown to be beneficial to capital market participants in many ways, reduced guidance has meaningful market implications. Our findings highlight a negative and possible unintended consequence of activist hedge funds' investment in firms, which provides some counterbalance to the numerous positive consequences documented in the prior literature on hedge fund activism.